HUBUNGAN POLA PEMBERIAN MAKAN DENGAN STATUS GIZI BALITA DI BAGAN PERCUT - Novita Aryani; Henny Syapitri (Jurnal Keperawatan Priority, 2021)
Toddlers are children who have reached the age of over one year or under five years, namely 24-60 months. This period is a challenge for parents because children find it difficult to eat, choose to eat, and like snacks with poor nutritional content such as instant noodles, which lead to a deficiency or excess intake of nutrients that can affect their nutritional status and health. The purpose of this study was to identify the relationship between feeding patterns and nutritional status in children under five in the Percut chart. The research design used in this study was cross-sectional. The population in this study was 67 people in Chart Percut with a sample size of 25 people who were taken using a simple random sampling technique. This study used a feeding pattern questionnaire and a z-score table. The results of the study were based on statistical analysis using the chi-square test with a significance level of <0.05, the result was p = 0.037. A P-value less than 0.05 indicates H1 is accepted and H0 is rejected, meaning that there is a relationship between feeding patterns and nutritional status in children under five in Percut Sei Tuan District, Deli Serdang Regency. The correlation coefficient (r) = 0.069, which means that it shows a strong relationship. The value of r is positive, which means that the more appropriate the feeding pattern, the better the nutritional status of the toddler.